4CPS-211 Adherence and interactions in patients treated with abiraterone and enzalutamide. (24th March 2020) - Tarazona Casany, MV; Perez, P; Monte, E; Cuellar, MJ
Abstract : Background and importance: Prostate cancer is a common tumour in elderly men. Treatment with abiraterone and enzalutamide increase survival and therefore it is important to assess adherence and interactions of these treatments. Aim and objectives: Our objective was to determine adherence to abiraterone or enzalutamida and interactions in patients with castration resistant prostate cancer (CRPC). Material and methods: This retrospective observational study included patients with CRPC receiving abiraterone or enzalutamide for at least 4 months. Demographic data were obtained from the computerised medical history. Adherence was measured by combining the Morisky–Green questionnaire and the dispensing record. Search and classification of the interactions was obtained from Drugs.com Results: Thirty-seven patients were included, with an average age of 74 years (SD 5). The average number of medications consumed by these patients was 7 (SD 2.5). Comorbidities averaged 5 per patient. All patients were adherent according to the Morisky–Green questionnaire, and combined with the dispensing records, adherence to abiraterone was 85% and 92% to enzalutamida. Pharmacological interactions were major interactions in 21% of cases, of which the most frequent was amiodarone and abiraterone. Moderate interactions occurred in 65% of patients, the most frequent being enzalutamide with lipid lowering agents (atorvastatin, simvastatin) and enzalutamide with proton pump inhibitors (omeprazole, esomeprazol): 14% of patients had no drug interactions. Conclusion and relevance: In these patients, good adherence to enzalutamide and abiraterone was found. All interactions classified as major were monitored. All patients with CRPC required pharmaceutical care. References and/or acknowledgements: No conflict of interest.